Speech Disorder of Dementic Sufferer by EFL Student at SLB BC Kepanjen Malang: A Psycholinguistic Study - Hayat, Najmuddin (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
ABSTRACT This study aims to analyze the speech disorder experienced by EFL student at SLB BC Kepanjen who suffer from dementia. Dementia is characterized by a progressive decline in cognitive abilities that affects communication and language skills. This research uses a descriptive qualitative method with a case study method. Data was collected from recorded conversations with a student with the initials MB, aged nineteen, who was diagnosed with dementia. Fifteen expressions identified based on Van Riper's (2003) theory were analyzed. From the analysis, it was found that the student experienced three types of speech impairment viz: phonation, articulation, and symbolization disorders. Out of the total fifteen phrases analyzed, seven were found to be in phonation disorder, which was the dominating finding, five phrases were identified as Articulation disorder. Then, three phrases showed symbolization disorder. This study emphasizes the need for more adaptive educational approaches and training for teachers in effective communication techniques. Furthermore, the results of this study indicate that speech impairment in EFL student at SLB BC Kepanjen is strongly influenced by the progressive condition of dementia. With a better understanding of the challenges student face, educators can provide more effective support to help student overcome language difficulties and improve their overall learning experience. This study opens up opportunities for future research into the long-term impact of dementia on language learning and the effectiveness of interventions implemented.